Kode Vicious the doctor is in. - Neville-Neil, George (New York ACM, 2005)
A koder with attitude, KV answers your questions. Miss Manners he ain't.
Keywords: Software; Software Engineering; Design tools and techniques; Modules and interfaces; Programming techniques; Miscellaneous; Coding tools and techniques; Theory